Examining The Marriage Practices of Ahmadiyah at Transito Refugee Camp In Mataram: A Study of Khi and State Recognition - Apip, Apipuddin; Padli, Erwin; Muliadi, Erlan; Aprillah, Ahmad (JURNAL PENELITIAN KEISLAMAN, 2023)
This research focuses on two main objectives. Firstly, it aims to evaluate the marriage of Ahmadiyah in accordance with the provisions in the Compilation of Islamic Law. Secondly, it aims to identify the form of support and the role of the state in providing legal certainty to the marriage of Ahmadiyah refugees in Transito Mataram. This study employed a qualitative-descriptive research design with a phenomenological approach. The findings indicate that Ahmadiyah refugees in Transito Mataram conducted marriages in accordance with the provisions of KHI, which suggests that their marriages were valid under Islamic law. The role of the state in the marriage of Ahmadiyah Refugees in Transito Mataram is evident through the existence of marriage registration for Ahmadiyah Refugees and the Prospective Bride Course provided to prospective couples by the Office of Religious Affairs which represents the presence of state.